USING OF THYMUS VULGARIS EXTRACTS TO CONTROL THE SNAIL VECTOR IN SCHISTOSOMIASIS (Part II) - & et al., Al-Obaidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The aim of this study is to determine the toxicity of Thymus Vulgaris aquatic plant extracts comparing with copper sulfates against Bulinus truncatus the vector of urinary Bilharziasis. Samples of the snails were collected from a site in Al-Rasheed district (30 km) southern of Baghdad.  The isolation, identification, and acclimatization made in the laboratory. Many toxic parameters as NOEL (Non-Observed Effect Level), Threshold, EC (Effective Concentration) and LC (Lethal Concentration) levels were determined in this study. The EC50 of T. vulgaris and Copper sulfates to B. truncatus were (8.4, and 0.9g/L) respectively. The LC50 of T. vulgaris and Copper sulfates to B. truncatus were (18.7, and 2.2 g/L) respectively. The study showed that the T. vulgaris extracts were less effective than CuSO4. The results improved that the toxicity of extracts was concentration and time dependent. This work concluded the ability to use the target extracts in control of snails the middle host of the cause of urinary Schistosomiasis.